Total Ammoniacal Nitrogen Biofiltration of Wastewaters from Aquaculture Systems Using Macrocystis Spp - Montalvo-Martinez, S (2013)
The results of total ammoniacal nitrogen (NH3 + NH4 +) removal in aquaculture systems using two experimental sets, aquatic seedlings produced in laboratory controlled conditions and wild seaweed (Macrocystis spp.) in reproductive state, are shown in this work. Biofiltration assays were carried out using a load of total ammoniacal nitrogen (TAN) of 1 mg/L. Absorption rates were measured taking into account a previous surface characterization, which gave values of 44 ± 14 cm2/g and 18 ± 6 cm2/g for aquatic seedlings and wild algae, respectively. The following parameters were measured during the experimental runs: temperature, pH, O2, illuminance or light intensity, salinity and total solids. TAN removals of 61% and 70% were achieved for the seedlings and Macrocystis spp., respectively, after 17 h of treatment. The TAN absorption results were expressed as a function of surface and mass achieving the following values: 3.0 nmol N cm-2 h-1 and 111 nmol N g-1 h-1 for the seedlings, and 6.9 nmol N cm-2 h-1 and 122.4 nmol N g-1 h-1 for the macroalgae. In the light of these biofiltration processes, the initial TAN concentration decreased by 90% for the seedlings and wild algae over approximately 110 and 41 h, respectively. In addition, TAN removals achieved with Macrocystis spp. were always higher than those obtained with aquatic seedlings for the same operating periods. © 2013 Copyright Taylor and Francis Group, LLC.